Penalizing democracy: punitive politics in neoliberal Mexico - Müller, Markus-Michael (Crime, law and social change, 2016)
During the last two decades Mexico witnessed a hitherto unparalleled increase in its prison population and an outright punitive turn in local politics. In analyzing these developments, the article argues that the latter are inseparable from different securitization processes emerging from the articulation of democratic politics and neoliberal rationalities of economic governance. The article analyzes three key policy areas—as well as the related (in)securitization processes, their legal-institutional manifestations, and the penalizing consequences—which are paradigmatic examples of the growing punitiveness of Mexican politics: (a) the securitization process related to the war on drugs, (b) the securitization of urban space, and (c) the securitization of migration. In analyzing these three instances of (in)securitization, the article stresses that far from being homogenous and even developments, (in)securitization as well as the underlying processes of neoliberalization and democratization are policy- and place-specific phenomena that produce an uneven punitive topography that shapes the neoliberal present in democratic Mexico.